Life Cycle Assessment of Wood Pellet Product at Korintiga Hutani company, Central Kalimantan, Indonesia - Iswanto; Dodik Ridho Nurrochmat; Ulfah Juniarti Siregar (Institut Pertanian Bogor (IPB University), 2021)
Climate change has forced human being to adapt in fulfilling their energy needs sustainably. In Indonesia, forestry activities has been considered as an emission rather than carbon sink. This study aims to analyze the inputs, outputs, and potential environmental impacts of wood pellet production in a forest company using life cycle assessment (LCA). The wood pellet is made from Eucalyptus pellita plantation. Analysis was made for 1 planting cycle or 6 years, and allometric equations were used to estimate the ability of industrial timber plantation forest to absorb CO2. Production of wood pellet starting from plantation requires inputs as follows: diesel fuel, electricity, NPK and other fertilizers, pesticides, and electrical energy. Those inputs produced emissions, of which the largest was N2O of 551.2927 kg, followed by NH3 of 7.5275 kg generated from NPK fertilizer. Another was PO43- amounted at 0.1792–0.2229 kg from liquid fertilizers and pesticides. Potential acidification came from 13.3675 kg SO2 eq, and eutrophication of 0.4021 kg PO43- eq. The greenhouse gas (GHG) emission was 678.0270 kg CO2 eq from the plantation activities, especially from diesel-based energy consumption, while wood pellet mills only released 0.1053 kg CO2 eq of GHG emissions. Thus, total emissions from 6 years' time of wood pellet production are much lower compared to the average CO2 absorbed by the plantation forest, of which annually is 36.34–67.69 ton ha-1year-1.